3D Blade Hydraulic Design Method of the Rotodynamic Multiphase Pump Impeller and Performance Research. (26th February 2014) - Zhang, Yongxue; Zhang, Jinya; Zhu, Hongwu; Cai, Shujie
Abstract : A hydraulic design method of three-dimensional blade was presented to design the blades of the rotodynamic multiphase pump. Numerical simulations and bench test were conducted to investigate the performance of the example impeller designed by the presented method. The results obtained from the bench test were in good agreement with the simulation results, which indicated the reasonability of the simulation. The distributions of pressure and gas volume fraction were analyzed and the results showed that the designed impeller was good for the transportation of mixture composed of gas and liquid. In addition, the advantage of the impeller designed by the presented method was suitable for using in large volume rate conditions, which were reflected by the comparison of the head performance between this three-dimensional design method and another one.